Effect of Petroleum Hydrocarbon on Physiological and Biochemical Parameters in an Estuarine Clam, Paphia malabarica - Modassir, Yasmin; Ansari, Azra (Fishery Technology, 2025)
Commercial grade diesel oil was used as a source of petroleum hydrocarbon to study the toxic effect of petroleum hydrocarbons on physiological and biochemical parameters in an estuarine bivalve, Paphia malabarica. The results of the investigation revealed the adverse effect of diesel oil on the growth condition index and biochemical constituents. The growth was affected resulting in reduction of about 30% in the average growth rate after 30 davs. The impact was more with higher concentration. There was reduction in the values of organic carbon and nitrogen. The biochemical constituents such as protein and carbohydrate also showed slight decline while the lipid content increased marginally. The results suggest that exposure to petroleum hydrocarbon may be deleterious to manv marine and estuarine organisms and may change the physiological and biochemical processes, depending on its bioavailability and exposure concentration.